FUNCTIONS OF SOCIETY'S EXPRESSIVE SPEECH ACTS TOWARDS COVID-19 SURVIVORS - Usman, Usman; Ramadhani, Fitrah (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This research was inspired by discourse analysis of human expressive speech act as thepart of Illocutionary act. This study aims to analyze speech act to finally describe the function ofthe society‟s expressive speech acts towards Covid-19 survivors. Using qualitative method, thisresearch was conducted in Gowa Regency, South Sulawesi through observation, interviews, andrecording as data collection techniques. The instruments consist of the main instrument, which wasresearchers themselves, and supporting instruments including data analysis guides, observation,interview, and recording devices. The data was in the form of expressive words, phrases, clausesand sentences expressed by the society when communicating and interacting with Covid-19survivors. The data source was generally from the society without Covid-19 and from thesurvivors of Covid-19 who receive expressive speech act from the other. The results reveal thatthere were various function of expressive speech acts used among society during Covid-19pandemic such as the function of complaining, cursing, doubting, yelling, and fearing function.Those functions implicitly were represented to prevent Covid-19 survivors from repeating theirmistakes. Meanwhile, the functions of apologizing, condolences, motivating, and greeting wererepresented so that the people without Covid-19 can be the cause of healing for sufferers andsurvivors of Covid-19.